POLITIK HUKUM PENYELESAIAN PELANGGARAN HAM BERAT DI ERA PEMERINTAHAN JOKOWI-JK - Radjab, Syamsuddin (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2018)
The legal political study of law enforcement in the field of human rights is a government legal political policy under the Jokowi-JK government to determine the direction and steps to be applied in resolving cases of serious human rights violations that occurred in the past as promised in its 2014 political campaign. The discourse on the resolution of gross human rights violations is a plausible promise during the campaign period so that it was elected president and was installed on October 20, 2014. In practice, during the 4 years of Jokowi-JK's administration, the campaign promises to date have not been realized while his administration was 1 more years. In this regard, under the Jokowi-JK government, the problem of resolving gross human rights violations is limited to political jargon and has not become a legal slogan in the enforcement of law and human rights and weak political will to realize this promise. This research is descriptive-analytical with a normative juridical approach which is carried out through library and field research, especially criticism of public discourse by contextualizing the sociological-political reality.